Point of Law. Comparative Legal Analysis of the Legal Status of Deputies of Belgium and France with Parliamentarians of the Russian Federation - Melnikov, Victor Yu.; Seregin, Andrei V.; Cherkasova, Marina A.; Akhrameeva, Olga V.; Danilova, Valeria A. (Opción)
The article deals with theoretical and legal problems of constitutional guarantees of parliamentary activity on the example of Belgium and France. The authors believe that the combination of legal guarantees with the need for legal responsibility of modern parliamentarians as representatives of the people is most harmoniously enshrined in French legislation, which is advisable to use as a model when reforming the system of people’s representation of the Russian Federation.